(untitled) (Applied Biological Research, 2025)
Perineal hernia is frequently encountered in intact male dogs. While various surgical approaches exist, this study was aimed to compare the outcomes of autologous tunica vaginalis hernioplasty and polypropylene mesh hernioplasty in twelve dogs, divided equally into two groups. Seven dogs had bilateral perineal hernias, while five dogs had unilateral hernia, of which four were on the right side and one on the left side. The omentum was the most commonly herniated structure (50%), followed by the prostate, urinary bladder, and rectum. Recurrence was observed in two dogs treated with tunica vaginalis grafts and in three dogs treated with polypropylene mesh. In conclusion, the tunica vaginalis grafting technique demonstrated lower recurrence rates, suggesting greater therapeutic efficacy. Nonetheless, further research involving larger sample sizes and targeted management of postoperative complications such as tenesmus, straining, and urinary incontinence could enhance the overall success of the procedure.